Qubbet El-Hawa, 2016. Issue 1 (January 2016) - Bommas, Martin
Report of two short field seasons of the joint University of Birmingham/Egypt Exploration Society mission at Qubbet el-Hawa in February and September 2016. In the area of the northern necropolis, below the upper terrace of rock cut tombs, three excavation areas were identified that have not been investigated before. Among the monuments unearthed are a protection wall close to the edge of the cliff, a causeway leading to this wall, and the long-sought causeway of Sarenput I. Amongst the finds presented here, two Middle Kingdom reliefs and pottery are discussed in further detail